2018
DOI: 10.4172/1939-067x.1000154
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Autophagy for Neuroprotection in Ischaemic Stroke

Abstract: Autophagy is a highly regulated, catabolic process, through which macromolecules such as damaged organelles and proteins are degraded and recycled to maintain cellular homeostasis. Various studies have shown the role of autophagy activation in the brain cells such as astrocytes, microglia, neurons and capillary endothelial cells upon an ischaemic insult. The underlying mechanism and the role of autophagy in ischaemic stroke, however, are yet to be fully elucidated. Recent studies have suggested that insufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…MTT assay assesses mitochondrial catabolism and cell metabolic activity, which can be reduced in cells whilst retaining cell membrane integrity represented by LDH assay 28 . www.nature.com/scientificreports www.nature.com/scientificreports/ Next, the role of the PHD inhibitors on three major autophagic marker, LC3, p62 and Beclin1 was studied using rapamycin as a positive control inducer of autophagy 29 . Beclin1 plays an important role in induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTT assay assesses mitochondrial catabolism and cell metabolic activity, which can be reduced in cells whilst retaining cell membrane integrity represented by LDH assay 28 . www.nature.com/scientificreports www.nature.com/scientificreports/ Next, the role of the PHD inhibitors on three major autophagic marker, LC3, p62 and Beclin1 was studied using rapamycin as a positive control inducer of autophagy 29 . Beclin1 plays an important role in induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a self-catabolic process of damaged or dysfunctional cellular components, which are recycled for providing energy and nutrients 29 . A number of studies demonstrate that mild/moderate autophagy has a neuroprotective effect on ischaemic stroke whereas insufficient or excessive autophagy results in nerve damage and cell death 22,29 . A study by Park et al 38 showed ischaemic preconditioning (IPC) increased generation of autophagosomes and lysosomal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al [112] reported increased angiogenesis and neurogenesis and improved functional recovery following metformin treatment post tMCAo. Since AMPK coordinates control of cell growth and autophagy [113], the neuroprotective effects could be due to autophagy induced by metformin [114]. Furthermore, metformin has also been shown to inhibit NF-κB cascade and suppress neuroinflammation [115,116].…”
Section: Metforminmentioning
confidence: 99%
“…Rapamycin, a drug that induces autophagy, has been shown to confer neuroprotection in fly and mouse models of Huntington’s disease [114]. However, if autophagic recycling becomes imbalanced, it can lead to neuronal cell death; thus, careful control of autophagy is vital [112, 115]. At present, it is not clear what specific modulation of autophagy is required for neuroprotection [115]; control of autophagy could be a promising future strategy, but further studies are required to establish its role and potential for therapeutic use.…”
Section: Neuroprotection In Gamentioning
confidence: 99%